A quasi-plane IrB18− cluster with high stability. Issue 10 (2nd March 2020) - Wei, Donghe; Ren, Mengxue; Lu, Cheng; Bi, Jie; Maroulis, George
Abstract : A quasi-plane anionic IrB18 − cluster with high stability is uncovered by a CALYPSO structural search method. Abstract : The structural evolution of neutral and anionic iridium-doped boron (B) clusters, IrB n 0/− with n = 10–20, has been studied by the Crystal structure AnaLYsis by Particle Swarm Optimization (CALYPSO) method and density functional theory (DFT) calculations. The IrB18 − cluster with a quasi-plane structure and high stability is uncovered. Molecular orbital (MO) and adaptive natural density partitioning (AdNDP) analyses indicate that the high stability of the IrB18 − cluster is attributed to the strong covalent interactions between the 5d orbitals of the Ir atom and the 2p orbitals of the surrounding B atoms. The present results offer new insights and considerably extend our understanding of the structural evolution and electronic properties of other metal-doped B clusters.